Progressive multifocal leucoencephalopathy after autologous bone marrow transplantation: a treatment option. (15th April 2011) - Ripellino, P; Comi, C; Mula, M; Varrasi, C; Conconi, A; Stecco, A; Brustia, D; Nasuelli, N; Savio, K; De Paoli, L; Cantello, R; Gaidano, G; et al.
Abstract : A patient with multiple myeloma was treated with high-dose chemotherapy followed by two autologous bone marrow transplantations (ABMTs). Nine months after the second ABMT the patient complained of severe left hemiparesis, paraesthesias, left homonymous visual field defects and gait ataxia. She was diagnosed with progressive multifocal leucoencephalopathy (PML) confirmed by detection of JC virus (JCV) DNA and prescribed cidofovir every other week and mirtazapine daily. Her symptoms and signs remained stable and after 6 months the JCV DNA was undetectable in the cerebrospinal fluid. Repeated MRI scans demonstrated the stabilisation of demyelinating lesion volume; after more than 2 years of follow-up the patient's neurological examination does not show significant variations. Combination of cidofovir and mirtazapine may be helpful in the treatment of PML in HIV-negative patients.